2016
DOI: 10.1097/sla.0000000000001675
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tracheal Occlusion for Severe Pulmonary Hypoplasia in Isolated Congenital Diaphragmatic Hernia

Abstract: FETO improves survival in isolated CDH with severe pulmonary hypoplasia compared with the standard perinatal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 30 publications
2
92
0
Order By: Relevance
“…Whether these results represent an improvement in survival of neonates with CDH compared to expectant management can only be assessed taking into account the severity of the disease based on prenatal prognostic factors [10] . It has previously been shown that there is a strong association between O/E LHR and survival, both for left and right CDH, and that liver herniation is an additional worsening prognostic factor in left-sided defects.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these results represent an improvement in survival of neonates with CDH compared to expectant management can only be assessed taking into account the severity of the disease based on prenatal prognostic factors [10] . It has previously been shown that there is a strong association between O/E LHR and survival, both for left and right CDH, and that liver herniation is an additional worsening prognostic factor in left-sided defects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that tracheal occlusion can indeed cause an increase in lung growth [51,52] and removing the balloon before birth has shown to be necessary for a better maturation of the lung by decreasing the apoptosis of the alveolar type 2 cells, which produce surfactant, an essential compound for lung function [53]. So far, FETO has been shown to improve survival rate in high-risk CDH patients, but at the cost of increased morbidity and premature delivery [54][55][56]. The results of the TOTAL trial will hopefully provide a more definitive answer.…”
Section: Treatment Of Pulmonary Vascular Defects In Cdhmentioning
confidence: 99%
“…TO for CDH in humans is typically placed at the 28th week of gestation and removed during the 34 th week. A meta-analysis of over 200 human fetuses treated with this approach demonstrated decreased mortality (5). While TO for CDH may gain more widespread acceptance in the coming years, there remains an urgent need to understand the cellular responses to CDH and TO so that targeted therapies may be developed to improve fetal lung development and to limit any undesirable effects of TO.…”
mentioning
confidence: 99%